Utilization of sweet potato solids for value-addition to chocolate ice cream (Indian Journal of Traditional Knowledge (IJTK), 2024)
Sweet potato is rich in carotenoids and fiber and confers sweetness to the product in which it is utilized. The aim of the research was to utilize sweet potato in the form of ‘osmo-vac’ dehydrated powder in medium-fat (6.0% fat) ‘chocolate ice cream’ for value-addition. Use of sweet potato powder (SPP) at 2.0 to 4.0% level did not affect the sensory quality of chocolate ice cream appreciably. SPP when used at 4.0% level in ‘medium-fat’ chocolate ice cream led to enrichment of the ice cream with b-carotene and fiber; it could replace 40.0% of milk fat and 10.0% of sugar in ice cream. Ice cream containing 4.0% SPP tended to have markedly higher total carbohydrates and total solids content as compared to control ‘medium-fat’ ice cream. Presence of SPP in ice cream led to slight impairment in its overrun. The ‘medium-fat’ chocolate ice cream prepared utilizing 4.0% SPP had sensory scores similar to those of ‘full-fat’ (10.0% fat) control ice cream. Ice cream is an ideal medium for utilizing sweet potato solids contributing to value-addition to the frozen delicacy.